379- مستقبل صناعة واستخدامات الطائرات المسيرة دون طيار - درون- لدعم التنمية والأمن القومي عالميًا ومحليًا: The Future of the Drone Industry and Its Uses in Supporting Development and National Security Globally and Locally - ماجد خشبة; علاء الدين زهران، مها الشال وأخرون (معهد التخطيط القومي, 2026)
تهدف الدراسة إلى تقييم فرص الاستفادة من صناعة واستخدامات الطائرات المسيرة دون طيار في مصر لدعم التنمية المستدامة والأمن القومي. وتستعرض الاتجاهات العالمية الحديثة في هذا المجال ودور الذكاء الاصطناعي في تطوير قدراتها وتوسيع استخداماتها. كما تعرض تجارب دول متقدمة ونامية وعربية للاستفادة من الدروس المستخلصة منها. وتركز على واقع صناعة واستخدام الطائرات المسيرة في مصر والأطر التشريعية والتنظيمية المرتبطة بها. وتختتم بتقديم إطار مقترح لتعظيم استفادة مصر من هذه التكنولوجيا في مجالي الصناعة والاستخدامات التنموية. This study assesses opportunities to maximize the benefits of the UAV industry and its applications in Egypt to support sustainable development and national security. It reviews recent international literature on both UAV manufacturing and developmental applications, highlighting the role of artificial intelligence in expanding their capabilities. The study analyzes global trends and experiences from developed, developing, and Arab countries to identify best practices relevant to Egypt. It also examines Egypt’s legislative framework, industrial capabilities, and current developmental uses of UAVs, supported by insights from an expert panel. Finally, the study proposes a framework to enhance Egypt’s utilization of UAVs in both industry and development based on global experiences and expert recommendations.